2016
DOI: 10.1007/s10551-016-3051-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Ethical Organisational Culture and Organisational Innovativeness: Comparison of Findings from Finland and Lithuania

Abstract: in fostering the organisational capacity to innovate. In this paper, a different context is taken to test hypothesized differences between the two multidimensional phenomena. The paper discusses the findings of 2 surveys in Finnish and Lithuanian public organisations (respectively, n FI =477 and n LT =757). Data analysis shows that ethical organisational culture affects organisational innovativeness, in particular process and behaviour innovativeness in both organisations. The findings suggest that some ethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…An ethical culture can foster organizational innovativeness in many ways, such as encouraging the formation of open, fair, and cooperative culture that might lead to increased sharing of ideas, and enhancing employees' positive self-evaluation and identification with their organization. Riivari et al (2012) and Riivari and Lämsä (2014) studied the link between ethical organizational culture and organizational innovativeness, and showed that the ethical virtues of congruency of management and supervisors can be particularly important features for the innovativeness of the organization, a result that was recently supported in another cultural context by Puč _ etait_ e et al (2016). These preliminary findings on the role of an ethical culture in organizational innovativeness suggest that ethical virtues are meaningful in supporting organizational innovativeness.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…An ethical culture can foster organizational innovativeness in many ways, such as encouraging the formation of open, fair, and cooperative culture that might lead to increased sharing of ideas, and enhancing employees' positive self-evaluation and identification with their organization. Riivari et al (2012) and Riivari and Lämsä (2014) studied the link between ethical organizational culture and organizational innovativeness, and showed that the ethical virtues of congruency of management and supervisors can be particularly important features for the innovativeness of the organization, a result that was recently supported in another cultural context by Puč _ etait_ e et al (2016). These preliminary findings on the role of an ethical culture in organizational innovativeness suggest that ethical virtues are meaningful in supporting organizational innovativeness.…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, this study emphasizes ethical virtues and organizational innovativeness in this organizational and societal context. Since empirical, specifically qualitative, research about ethics and innovativeness is not so common in current research, even if ethics is often considered to be important for organizations (Collier 1998;Crane and Matten 2007;Huhtala et al 2011;Kaptein 2008Kaptein , 2009Kaptein , 2010Kaptein , 2011Paine 1997;Puč _ etait_ e et al 2010;Riivari et al 2012;Sims and Brinkmann 2009;Sinclair 1993;Solomon 2004;Treviño 1990;Treviño et al 1998), and is therefore relevant to investigate, we suggest that the topic would merit more research in other organizational and societal contexts. Additionally, cross-cultural comparisons would be interesting.…”
Section: Research Limitations and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the aim of our study is to find out in what respect team ethical cultures differ (when they do differ), we have to use the CEV model because so far it is the only multidimensional scale of ethical culture. To preserve construct validity, the choice of the CEV model also reflects its recent use in many empirical studies on ethical culture (e.g., Huhtala et al 2015Huhtala et al , 2016Huhtala et al , 2018Kangas et al 2016Kangas et al , 2017Pučėtaitė et al 2016;Riivari and Lämsä 2014;Zaal et al 2017).…”
Section: Team Ethical Culturementioning
confidence: 99%
“…Organizational creativity is an organizational capability for companies to integrate and exchange information to generate new knowledge (Duan, 2017;Fang et al, 2015;Pucetaite et al, 2016). Based on the perspective of organizational knowledge, organizations fi rst need to identify new opportunities to initiate the process of "knowledge creation"; then the organization needs to integrate existing knowledge with new knowledge, or integrate existing knowledge in new ways to form new knowledge architecture (Pastor Seller & Sanchez Millan 2014).…”
Section: Organizational Improvisation and Organizational Creativitymentioning
confidence: 99%